Austrotinodes Schmid, a South and Central American caddisfly genus, newly recorded in Australia, with the description of new species (Trichoptera: Ecnomidae) - Cartwright, David I. (Zootaxa, 2009)
Descriptions, keys and a checklist are provided for males of 11 ecnomid caddisfly species, all new to Australia. Females of 4 species are also described. These are placed in the genus Austrotinodes Schmid. The new species are: Austrotinodes bibu, A. bifurcatus, A. camurus, A. doota, A. glaya, A. gorom, A. mubar, A. pandus, A. theischingeri, A. varus and A. yalga. Austrotinodes with a total of 38 species previously recorded from South and Central America and southern USA, is here recorded from Australia for the first time.